Influence of Soda Pulping Variables on Properties of Pineapple (Ananas comosus Merr.) Leaf Pulp and Paper Studied by Face-Centered Composite Experimental Design - Jantharat Wutisatwongkul; Nandh Thavarungkul; Jirawan Tiansuwan; Preecha Termsuksawad (Advances in Materials Science and Engineering)
Face-centered composite design (FCC) was used to study the effect of pulping variables: soda concentration (4-5 wt%), temperature (90–130°C), and pulping time (20–60 min) on the properties of pineapple leaf pulp and paper employing soda pulping. Studied pulp responses were screened yield and lignin content (kappa number). Paper properties, which include tensile index, burst index, and tear index, were also investigated. Effects of the pulping variables on the properties were statistically analyzed using Minitab 16. The optimum conditions to obtain the maximum tensile index were soda concentration of 4 wt%, pulping temperature of 105°C, and pulping time of 20 min. The predicted optimum conditions provided tensile index, burst index, tear index, screened yield, and kappa number of 44.13 kN·m/kg, 1.76 kPa·m2, 1.68 N·m2/kg, 21.29 wt%, and 28.12, respectively, and were experimentally confirmed.